2018
DOI: 10.1016/j.bbi.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide counteracts autistic-like behaviours in BTBR T+tf/J mice: Contribution of central and peripheral mechanisms

Abstract: Autism spectrum disorders (ASD) are a group of heterogeneous neurodevelopmental conditions characterized by impaired social interaction, and repetitive stereotyped behaviours. Interestingly, functional and inflammatory gastrointestinal diseases are often reported as a comorbidity in ASDs, indicating gut-brain axis as a novel emerging approach. Recently, a central role for peroxisome-proliferator activated receptor (PPAR)-α has been addressed in neurological functions, associated with the behaviour. Among endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 51 publications
1
72
0
Order By: Relevance
“…In another rodent model of ASD, the BTBR T + tf/J (BTBR) mouse, PEA reverted the altered phenotype and improved ASD-like behavior through a PPAR-α activation. This effect was accompanied by decreased levels of inflammatory cytokines in serum, hippocampus, and colon [53]. PEA administration restored the hippocampal BDNF signaling pathway in BTBR mice and improved mitochondrial dysfunction, which has been observed in ASD (Tables 1 and 2) [53].…”
Section: Neurodevelopmental Disordersmentioning
confidence: 73%
“…In another rodent model of ASD, the BTBR T + tf/J (BTBR) mouse, PEA reverted the altered phenotype and improved ASD-like behavior through a PPAR-α activation. This effect was accompanied by decreased levels of inflammatory cytokines in serum, hippocampus, and colon [53]. PEA administration restored the hippocampal BDNF signaling pathway in BTBR mice and improved mitochondrial dysfunction, which has been observed in ASD (Tables 1 and 2) [53].…”
Section: Neurodevelopmental Disordersmentioning
confidence: 73%
“…The enteroprotective effect of PEA passes through the direct or indirect activation of PPAR-α and CB2 receptors [138][139][140][144][145][146][147], whose expression has also been confirmed in the canine and feline gastrointestinal tract [101,109]. It has also recently been found that PEA restores the intestinal barrier permeability via the regulation of intercellular junctions [139,146,[148][149][150], and reduces inflammatory cell recruitment, i.e., macrophages and neutrophils, during experimental intestinal injury [138,144,147,[151][152][153][154]. PEA administration also decreased viral-induced diarrhea [140] and normalized intestinal motility in a post-inflammatory accelerated transit model [145].…”
Section: Gastrointestinal Tractmentioning
confidence: 91%
“…93 Accordingly, a non CB 1 receptor-activating NAE, N-palmitoylethanolamine, which activates PPAR-a and, indirectly, TRPV1, was recently shown to produce therapeutic effects in models of ASD or vitamin D-deficiency-induced pain, and at the same time reduce systemic or central inflammation associated with disrupted gut microbiota composition. 95,96 Evidence also exists for beneficial gut microbiota modulation by another non-eCB NAE, N-oleoylethanolamine, 97,98 as well as by the TRPV1 agonist capsaicin. 99 In summary, alterations not only in the eCBome but also in its emerging tight bidirectional relationships with the gut microbiome, are starting to be viewed as a potentially important mechanism in the etiology, progress, and symptoms of neuropsychiatric disorders.…”
Section: Thcvmentioning
confidence: 99%